Associations of low handgrip strength with cancer mortality: a multicentre observational study. Issue 6 (10th September 2020) - Zhuang, Cheng‐Le; Zhang, Feng‐Min; Li, Wei; Wang, Kun‐Hua; Xu, Hong‐Xia; Song, Chun‐Hua; Guo, Zeng‐Qing; Shi, Han‐Ping
Abstract: Background: Handgrip strength (HGS) is associated with poor clinical outcomes, including all‐cause, non‐cardiovascular, and cardiovascular mortalities. The published cut‐off points for HGS are mostly based on community populations from Western countries, lacking information on cancer patients from China. The objective of this study was to establish sex‐specific cut‐off points for Chinese cancer patients and investigate the effect of low HGS on cancer mortality. Methods: We did a retrospective cohort study of patients who were diagnosed with malignant cancer from June 2012 to December 2018. HGS was measured using a hand dynamometer in 8257 cancer patients. Optimal stratification was used to solve threshold points. The hazard ratio (HR) of all cancer mortality and cancer‐specific mortality was calculated using Cox proportional hazard regression models. Results: Among all participants, there were 3902 (47.3%) women and 4355 (52.7%) men. The median age was 58 years old. The cut‐off points of HGS to best classify patients with respect to time to mortality were <16.1 kg for women and <22 kg for men. Low HGS was associated with overall cancer mortality in both women and men [HR = 1.339, 95% confidence interval (CI) = 1.170–1.531, P < 0.001; HR = 1.346, 95% CI = 1.176–1.540, P < 0.001, respectively]. For specific cancer types, low HGS was associated with breast cancer (HR = 1.593, 95% CI = 1.230–2.063, P < 0.001) in women, and lung cancer (HR = 1.369, 95% CI = 1.005–1.866, P = 0.047) and colorectal cancer (HR = 1.399, 95% CI = 1.007–1.944, P = 0.045) in men. Conclusions: On the basis of our sex‐specific cut‐off points, low HGS was strongly associated with cancer mortalities. These results indicate the usefulness of HGS measurement in routine clinical practice for improving patient assessments, cancer prognosis, and intervention.